Multivariate analysis of soil attributes of apple orchards under conventional and organic production systems - Maluche-Baretta, Carolina Riviera Duarte; Amarante, Cassandro Vidal Talamini do; Klauberg Filho, Osmar (Pesquisa Agropecuaria Brasileira, 2006)
This study was carried out in apple orchards under conventional and organic production systems, aiming to identify differences between them, in terms of soil microbiological and chemical attributes, with multivariate canonical discriminant analysis (CDA) and canonical correlation analysis (CCA). Soil samples were collected under the canopies of 24 plants which were arranged in a 45x54 m grid, in conventional and organic orchards. Samples were collected in two seasons and microbial biomass carbon (MBC), total organic carbon (TOC), microbial biomass nitrogen (MBN), total nitrogen (TN), MBC:TOC ratio, MBN:TN ratio, basal respiration (C-CO2), and metabolic quotient (qCO2), and soil chemical attributes determined. The canonic discriminant analysis identified MBC as the most important microbiological attribute that discriminates orchard management systems, followed by qCO2 and MBN:TN rate. The microbiological and chemical attributes related to carbon were more sensitive to the orchard management systems than attributes related to nitrogen. The canonical correlation between microbiological and chemical attributes was highly significant, with a higher contribution of MBC for microbial attributes, and of pH H2O and aluminium for chemical attributes.
Keywords: soil quality; microbial activity; microbial biomass carbon; microbial biomass nitrogen